2021
DOI: 10.3389/fmicb.2021.696680
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus Persistence and/or Replication in the Peripheral Blood Mononuclear Cells of Acute HEV-Infected Patients

Abstract: Graphical AbstractFlow of the study design: Blood collected from acute HEV patients were fractiontated into plasma and PBMCs. Plasma was used for cytokine assay. RNA was extracted from the PBMCs and used for determinaton of viral load, detection of (+) and (−) HEV RNA strands, and gene expression assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In a parallel line, several studies showed the necessity of testing HEV markers before diagnosing cases as DILI [131,132]. Besides, the detection of HEV in patients' PBMCs and urine, but not semen, indicates that the viral isolates circulating in Egypt mediate extrahepatic manifestations [22,133].…”
Section: Recent Findings On the Status Of Hev Infection In Egyptmentioning
confidence: 99%
See 1 more Smart Citation
“…In a parallel line, several studies showed the necessity of testing HEV markers before diagnosing cases as DILI [131,132]. Besides, the detection of HEV in patients' PBMCs and urine, but not semen, indicates that the viral isolates circulating in Egypt mediate extrahepatic manifestations [22,133].…”
Section: Recent Findings On the Status Of Hev Infection In Egyptmentioning
confidence: 99%
“…HEV-1 and HEV-3 isolates were reported in Egypt [17][18][19]. Limited sequence data for HEV isolates were identified in Egypt and most HEV genotype 1 isolates were categorized into subtypes 1a, 1b, 1e and 1f [17,18,[20][21][22]. Rocahepevirus ratti incudes rat-derived HEV isolates which were recently reported with human infections [4,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…This virus is currently considered the most common cause of acute hepatitis worldwide; it can lead to severe illness in pregnant women and patients with liver disease and chronic infections in immunosuppressed individuals [ 2 ]. Notably, its recently recognized ability to infect multiple cell types and the adverse effects observed in diverse tissues due to infection support the notion that hepatitis E might be considered a systemic disease rather than solely a liver disease [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%